Phase behavior of cationic amphiphiles and their mixtures with helper lipid influences lipoplex shape, DNA translocation, and transfection efficiency. - Zuhorn, Inge S (2002)
Cationic lipids are widely used for gene transfection, but their mechanism of action is still poorly understood. To improve this knowledge, a structure-function study was carried out with two pyridinium-based lipid analogs with identical headgroups but differing in alkyl chain (un)saturation, i.e., SAINT-2 (diC18:1) and SAINT-5 (diC18:0). Although both amphiphiles display transfection activity per se, DOPE strongly promotes SAINT-2-mediated transfection, but not that of SAINT-5, despite the fact that DOPE effectively facilitates plasmid dissociation from either lipoplex. This difference appears to correlate with membrane stiffness, dictated by the cationic lipid packing in the donor liposomes, which governs the kinetics of lipid recruitment by the plasmid upon lipoplex assembly. Because of its interaction with the relatively rigid SAINT-5 membranes, the plasmid becomes inappropriately condensed, which results in formation of structurally deformed lipoplexes. This structural deformation does not affect its cellular uptake but, rather, hampers plasmid translocation across endosomal and/or nuclear membranes. This is inferred from the observation that both lipoplexes effectively translocate much smaller oligonucleotides into cells. In fact, SAINT-5/DOPE-mediated transfection is greatly improved when, before lipoplex assembly, the plasmid is stabilized by condensation with polylysine. The results emphasize a role of the structural shape of the plasmid in gaining cytosolic/nuclear access. Moreover, it has been proposed that such a translocation is promoted when the lipoplex adopts the hexagonal phase, and data are presented that demonstrate that the lamellar SAINT-5/DOPE lipoplex adopts such a phase after its interaction with acidic phospholipid-containing membranes.